THE EFFECTIVENESS COMPARISAN OF SCIENTIFIC LEARNING WITH COOPERATIVE LEARNING STUDENT TEAM ACHIEVEMENT DIVISIONS (STAD) AND JIGSAW IN TERMS OF STUDENTS’ MATHEMATCS LEARNING ACHIEVEMENT OF JUNIOR HIGH SCHOOL GRADE VII - Dewi Saputri; Heri Retnawati (Universitas Negeri Yogyakarta, 2017)
This study aimed to: (1) find out the effectiveness of scientific learning with cooperative learning STAD in terms of students’ mathematics learning achievement, (2) find out the effectiveness of scientific learning with cooperative learning Jigsaw in terms of students’ mathematics learning achievement, and (3) find out which one is more effective between scientific learning with cooperative learning STAD and scientific learning with cooperative learning Jigsaw in terms of students’ mathematics learning achievement. This study was a quasi-experimental research with the nonequivalent pretest-posttest group design. The study population included all students of grade VII in SMP Negeri 3 Mlati and the sample was class VII A and class VII B which were randomly selected. Data were analyzed by one sample t-test and independent sample t-test with significance value of 5%. The results of this study showed that: (1) scientific learning with cooperative learning STAD is effective in terms of students’ mathematics learning achievement, (2) scientific learning with cooperative learning Jigsaw is effective in terms of students’ mathematics learning achievement, and (3) scientific learning with cooperative learning STAD is not more effective than scientific learning with cooperative learning Jigsaw in terms of students’ mathematics learning achievement.Keywords: scientific learning, cooperative learning, STAD, Jigsaw, learning achievement